A case of granulomatosis with polyangiitis and pyoderma gangrenosum successfully treated with infliximab and rituximab. (27th January 2014) - Donmez, Salim; Pamuk, Omer N.; Gedik, Mustafa; Ak, Recep; Bulut, Gulay
Abstract Here, we present a young male patient who was admitted with alveolar hemorrhage, arthritis and cutaneous lesions, who later developed bilateral orbital involvement and pyoderma gangrenosum (PG). He also had pathergy test positivity. The patient was refractory to conventional immunosuppressive therapy. Therefore, multiple devastating PG lesions and disease activity in granulomatosis with polyangiitis (GPA) were controlled with infliximab. Later, rituximab was used with success to prevent recurrence of symptoms. The relationship of PG with various autoimmune diseases is known; however, PG in GPA has been only rarely reported. Biologic agents might prove to be effective in GPA and PG patients who are refractory to standard immunosuppressive therapy.